2016
DOI: 10.1016/j.cej.2015.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Novel tree-like WO 3 nanoplatelets with very high surface area synthesized by anodization under controlled hydrodynamic conditions

Abstract: In the present work, a new WO 3 nanostructure has been obtained by anodization in a H 2 SO 4 /NaF electrolyte under controlled hydrodynamic conditions using a Rotating Disc Electrode (RDE) configuration. Anodized samples were analyzed by means of Field Emission Scanning Electronic Microscopy (FE-SEM), Confocal Raman Microscopy and photoelectrochemical measurements. The new nanostructure, which consists of nanoplatelets clusters growing in a tree-like manner, presents a very high surface area exposed to the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…For example, tree-like globular clusters of WO 3 nanoplatelets were obtained in a 1.5 M H 2 SO 4 + 0.1 M NaF electrolyte and at different rotation velocities of the RDE. Figure 9 shows the FE-SEM images of the samples anodized in that electrolyte at different rotation velocities (0 and 375 rpm) [23,58]. It can be observed that in both cases, the nanostructures formed on the tungsten surface presented nanoplatelet morphology, as other authors reported when anodizing in similar acid electrolytes [53-55, 57, 58].…”
Section: Wosupporting
confidence: 56%
See 1 more Smart Citation
“…For example, tree-like globular clusters of WO 3 nanoplatelets were obtained in a 1.5 M H 2 SO 4 + 0.1 M NaF electrolyte and at different rotation velocities of the RDE. Figure 9 shows the FE-SEM images of the samples anodized in that electrolyte at different rotation velocities (0 and 375 rpm) [23,58]. It can be observed that in both cases, the nanostructures formed on the tungsten surface presented nanoplatelet morphology, as other authors reported when anodizing in similar acid electrolytes [53-55, 57, 58].…”
Section: Wosupporting
confidence: 56%
“…This decrease has been associated with the formation of a compact WO 3 layer on the electrode surface[19,23,58,60]. Subsequently, current density started increasing, indicating the dissolution of the WO 3 layer due to the effect of H + and F −[23,58,61]. This dissolution process resulted in the release of soluble cationic species, such as WO2 2+ (or [W(OH) 4 (H 2 O) 4 ] 2+ in its hydrated form) or [WF n ]…”
mentioning
confidence: 99%
“…In this way, 0D (dots), 1D (rods, whiskers, and fibres), 2D (plates, films), or 3D (large particles, blocks) WO 3 materials can be synthesized. Various types of nanostructured tungsten oxide have been reported, from simple, spherical nanoparticles [34] to WO 3 -based aerogel networks [35], quantum dots [36][37][38][39], nanostructured films [40] (including nanoplate films [41], nanorod films [42], honeycomb-structured films [43], and mesoporous films [44]), nanobelts [45], nanofibres [46], nanowires [30,46,47], bundle-like nanowires [30,48], nanonetworks [49], hollow spheres [50], macroporous spheres [51], wedge-like architectures [52], nanorods [53,54], nanocuboids [34], square nanoplates [55], nanosheets [56], nanoleaves [57], and urchin-like [30,58], flower-like [59][60][61], and tree-like nanostructures [62,63], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, WO3 can also absorb a part of the visible rays of the solar spectrum (its band-gap is Eg ≈ 2.6 eV, which corresponds approximately to a wavelength of ∼480 nm) [1][2][3][4]. Tungsten trioxide has been employed in technologically advanced fields, such as photoelectrochemistry and photodegradation of organic pollutants [4][5][6][7][8][9][10][11][12][13][14], dye-sensitized solar cells [15], gas sensors [16] or electrochromic devices [17][18][19].…”
Section: Introductionmentioning
confidence: 99%